2022
DOI: 10.3390/cimb44080253
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of MicroRNAs and Phytohormonal Signaling in Response to Drought Stress: A Review

Abstract: Phytohormones play an essential role in plant growth and development in response to environmental stresses. However, plant hormones require a complex signaling network combined with other signaling pathways to perform their proper functions. Thus, multiple phytohormonal signaling pathways are a prerequisite for understanding plant defense mechanism against stressful conditions. MicroRNAs (miRNAs) are master regulators of eukaryotic gene expression and are also influenced by a wide range of plant development ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 164 publications
0
20
0
Order By: Relevance
“…Our data suggest a clear relationship between ABA and both g s and Kh plant , where an increase in ABA triggers a decrease in g s and Kh plant until reaching a plateau ( Figure 4 D,F). Under WW conditions, either ABA and ACC concentrations, both related to drought resistance [ 47 , 78 , 79 , 80 , 81 ], kept similar concentration for all the studied rootstocks, both in the leaf and in the xylem. However, under WS conditions, increases in both phytohormones were rootstock-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our data suggest a clear relationship between ABA and both g s and Kh plant , where an increase in ABA triggers a decrease in g s and Kh plant until reaching a plateau ( Figure 4 D,F). Under WW conditions, either ABA and ACC concentrations, both related to drought resistance [ 47 , 78 , 79 , 80 , 81 ], kept similar concentration for all the studied rootstocks, both in the leaf and in the xylem. However, under WS conditions, increases in both phytohormones were rootstock-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that GA and CK are involved in plant photosynthesis regulation and source/sink balance [ 79 , 81 , 87 , 88 , 89 ]. Concretely, the movement of CK in the transpiration stream from the roots to the shoots stimulates the expression of photosynthesis genes [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations